Craniocervical posture and craniofacial morphology - Rosas Gomes, Liliane de C. [UNESP]; Carpio Horta, Karla O. [UNESP]; Gonçalves, João Roberto [UNESP]; Santos-Pinto, Ary dos [UNESP] (Oxford University Press, 2014)
The purpose of this study was to investigate the published evidence regarding the association between head and cervical posture and craniofacial morphology. An electronic search was conducted in PubMed, Medline, Embase, Scopus, and Cochrane databases up to 23 March 2012. Abstracts that seemed to correspond with the goals of this review were selected by a consensus between two independent reviewers. The original articles were retrieved and evaluated to ensure they match the inclusion criteria. Only articles that directly compared head and/or cervical posture with craniofacial morphology were included. A total of 84 articles were found of which 12 matched all inclusion criteria. Detailed analysis of the methodology in selected articles revealed quality scores ranging from weak to moderate. Nine articles were cross-sectional studies, whereas only three were longitudinal studies. The findings of selected articles were linked together in order to clarify the evidence on sagittal and vertical craniofacial features as well as growth prediction regarding different postures of the head and neck. On the basis of the data obtained from the literature, significant associations were found between variables concerning head and cervical posture and craniofacial morphology. However, the results of this systematic review suggest that such associations should be carefully interpreted, considering that correlation coefficients found ranged from low to moderate. Moreover, conflicting results were observed regarding some postural variables. Further longitudinal studies are required to elucidate the relationship between the development of craniofacial morphology and functional aspects of head and cervical posture.